Perinatal communication in extreme preterm birth: what can we learn from the British Association of Perinatal Medicine framework?. Issue 3 (March 2023) - Carr, James A.J.; Bates, Sarah; Mactier, Helen
Abstract: The 2019 British Association of Perinatal Medicine (BAPM) framework for the care of baby, mother and family at the time of extremely preterm birth moves away from care plans based on gestational age alone, and towards a more holistic approach which considers multiple risk factors and promotes individualized care. The framework places renewed emphasis on consultation and shared decision making with families and provides materials for clinicians to use in discussions with families about management and outcomes. This article explores the rationale behind the updated framework, summarizes recent developments in individualized clinical risk assessment and explores the provision of good quality palliative care where this is appropriate.